On dynamic stability of beam in two statements - L. A. Movsisyan; G. G. Nersisyan (National Academy of Sciences of Armenia)
The stability of beam in two cases when on one edge of it the force or displecement in form of periodical function is investigated. The equation of longitudinal vibrations is solved exactly and solution of stability equation is reduced to Couchy problem for infinite system. It is shown that in case of main parametric resonance one can acrount that compression force is constant along length of beam. Also is considered problem of stability when applied displecement is in impact form. Устойчивость стержня изучается в двух случаях, когда на конце задаётся сила или перемещение в виде периодической функции. Уравнение продольных колебаний решается точно, а решение уравнения устойчивости сводится к задаче Коши для бесконечной системы. Показано, что при главном параметрическом резонансе можно принять постоянство сжимающей силы по длине стержня. Рассмотрена также задача устойчивости, когда на конце стержня прилагается перемещение в виде удара.
Keywords: Physics